Strategi Guru Mata Pelajaran Sejarah Kebudayaan Islam dalam Upaya Pembentukan Karakter Siswa di Madrasah Aliyah Swasta Bustanul Ulum Guppi Kota Tebing Tinggi - Hasibuan, Fahrul Setiawan; Sazali, Anwar; Rambe, Mirza Syadat (STAI Tebing Tinggi Deli, 2024)
The purpose of the study is to determine the concept of character formation of students at the Bustanul Ulum GUPPI Private Islamic Senior High School, Tebing Tinggi City; To determine the Strategy of Islamic Cultural History Subject Teachers in Efforts to Form Student Character at the Bustanul Ulum GUPPI Private Islamic Senior High School, Tebing Tinggi City and To determine the obstacles faced by Islamic Cultural History Subject Teachers in Forming Student Character at the Bustanul Ulum GUPPI Private Islamic Senior High School, Tebing Tinggi City. This study is a qualitative study that explains in depth about what is obtained from others, either in written or oral form from people and observable behavior. The results of the study show that the concept of character formation of students at the Bustanul Ulum GUPPI Private Islamic Senior High School, Tebing Tinggi City is based on the integration of moral, ethical, and Islamic religious values ​​into all aspects of education. Character education in this madrasah is designed to shape students into individuals who have noble morals, have positive traits and natures, and behave in accordance with Islamic and national values. The strategy implemented by the subject teacher of Islamic Cultural History (SKI) at Bustanul Ulum GUPPI Private Islamic Senior High School in Tebing Tinggi City in an effort to form students' character focuses on the integration of moral and ethical values ​​into the learning materials. SKI teachers use an approach that involves telling inspiring stories from Islamic history, reflective discussions, and emphasizing the application of character values ​​in everyday life. SKI teachers also utilize key moments in teaching to instill values ​​such as honesty, hard work, and responsibility. In addition, teachers encourage active student involvement through discussions that allow them to relate the subject matter to personal experiences, so that character values ​​become more relevant and easier to understand.